Sewage Pollution in the Coastal Waters off Port Dickson, Straits of Malacca - Law, A. T.; Othman, Azahar (1990)
The distribution of fecal colifonn bacteria in the near-shore waters and coastal waters of Port Dickson was studied between August 1987 and August 1989. Although a significantly high level of fecal coliform bacteria was found in the near- shore waters, very low levels were detected in the sediments and in roastal waters between 0.5 km and 5 kIn away from the roast. The results indirate that the coastal waters of Port Dickson are suitable for recreational and aquaculture uses.